Effectiveness of targeting the NLRP3 inflammasome by using natural polyphenols: A systematic review of implications on health effects. (March 2023) - Wang, Taotao; Xu, Hong; Dong, Ruixia; Wu, Shanshan; Guo, Yuanxin; Wang, Dongxu
Graphical abstract: Highlights: Major dietary polyphenols as natural NLRP3 inhibitors are illustrated by chemical structure. Targeting the NLRP3 by polyphenols play a key role in its health effects. The inhibitory mechanisms on NLRP3 imparting therapeutic properties to polyphenols are detailed. Recent advances in clinical trials, and nano-delivery systems for targeting NLRP3 of polyphenols are discussed. Abstract: Globally, inflammation and metabolic disorders pose serious public health problems and are major health concerns. It has been shown that natural polyphenols are effective in the treatment of metabolic diseases, including anti-inflammation, anti-diabetes, anti-obesity, neuron-protection, and cardio-protection. NLRP3 inflammasome, which are multiprotein complexes located within the cytosol, play an important role in the innate immune system. However, aberrant activation of the NLRP3 inflammasome were discovered as essential molecular mechanisms in triggering inflammatory processes as well as implicating it in several major metabolic diseases, such as type 2 diabetes mellitus, obesity, atherosclerosis or cardiovascular disease. Recent studies indicate that natural polyphenols can inhibit NLRP3 inflammasome activation. In this review, the progress of natural polyphenols preventing inflammation and metabolic disorders via targeting NLRP3 inflammasome is systemically summarized. From the viewpoint of interfering NLRP3 inflammasome activation, the health effects of natural polyphenols are explained. Recent advances in other beneficial effects, clinical trials, and nano-delivery systems for targeting NLRP3 inflammasome are also reviewed. NLRP3 inflammasome is targeted by natural polyphenols to exert multiple health effects, which broadens the understanding of polyphenol mechanisms and provides valuable guidance to new researchers in this field.